Contextual Learning Model in Elementary Schools in Improving Learning Outcomes - Wulansari, Dian; Oktariani, Anita Putri; Pulungan, Marwan (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to improve students' cognitive learning outcomes by applying the Contextual Teaching and Learning learning model. Methodology: The research method used is Classroom Action Research, which consists of three cycles. The sampling technique was purposive sampling, with the sample being class III.B with a total of 31 students, consisting of 16 male and 15 female students. The research instruments used were observation sheets and student learning outcome assessment formats. The data analysis techniques used in this research are quantitative and qualitative data. Main Findings: The results of this research indicate that the application of the Contextual Teaching and Learning learning model can improve cognitive learning outcomes for theme 1 subtheme 2 in class III.B students, with learning completion results in cycle I 58%, cycle II 74.1%, cycle III 87% and post-test 90.3%, with a percentage of success requirements of 85%. Novelty/Originality of this study: The Contextual Teaching and Learning learning model can improve learning outcomes for theme 1 subtheme 2 class III.B at Elementary School 25 Palembang.